Down the Stairs Dystonia—A Novel Task‐Specific Focal Isolated Syndrome. Issue 1 (6th June 2016) - Menon, Suresh; Muglan, Jihad A.; Shimon, Laith; Stewart, Dwight; Snow, Barry; Hayes, Michael; Fung, Victor S.C.; Jog, Mandar S.
Abstract: View Supplementary Video 1 View Supplementary Video 2 View Supplementary Video 3 View Supplementary Video 4 View Supplementary Video 5 View Supplementary Video 6 Adult‐onset, task‐specific dystonia of the lower limb is a rare occurrence. In this report, the authors present 6 cases of task‐specific dystonia manifested only when going down the stairs. These patients were seen by 6 different neurologists from across Canada, Australia, and New Zealand, and all videos were reviewed by 1 movement disorders specialist who made the final diagnosis. Video description of each case is also presented. All 6 patients demonstrated dystonia of 1 of their lower limbs specifically only when going down the stairs. The remainder of the neurological examination was normal, and distractibility, inconsistency, fixed dystonia, or a premonitory urge were absent, making functional movement disorder and tic disorder unlikely. These 6 patients display a distinct, adult‐onset, focal isolated dystonia manifested only on going down the stairs that is recognizable as a new task‐specific dystonia of the lower extremity. Abstract : View Supplementary Video 1 View Supplementary Video 2 View Supplementary Video 3 View Supplementary Video 4 View Supplementary Video 5 View Supplementary Video 6